잠제 제원 및 평면배치에 따른 쇄파특성 - 이우동(Woo-Dong Lee); 허동수(Dong-Soo Hur); 허정원(Jung-Won Huh) (Han-guk haeyang gonghak hoeji (Online), 2010)
The aim of this study is to examine the effects of shape and plane arrangement of submerged breakwaters on 3-D wave breaking characteristics over them. First, the numerical model, which is able to consider the flow through a porous medium with inertial, laminar, and turbulent resistance terms, i.e. simulate directly WAve Structure Seabed/Sandy beach interaction, and can determine the eddy viscosity with a LES turbulent model in a 3-Dimensional wave field (LES-WASS-3D), has been validated by a comparison with Goda's equation for breaking wave heights. And then, using the numerical results, the wave breaking points over the crest of submerged breakwaters have been examined in relation to the shape and plane arrangement of submerged breakwaters. Moreover, the wave height distribution and upper flow around submerged breakwaters have been also discussed, as well as the distribution of the wave breaking points over the beach.